Home-based pre-surgical psychological intervention for knee osteoarthritis (HAPPiKNEES): a feasibility randomised controlled trial - das Nair, Roshan; Mhizha-Murira, Jacqueline R.; Anderson, Pippa; Carpenter, Hannah; Clarke, Simon; Groves, Sam; Leighton, Paul; Scammell, Brigitte E.; Topcu, Gogem; Walsh, David A.; Lincoln, Nadina B. (SAGE, 2018)
Objective: To determine the feasibility of conducting a trial of a pre-surgical psychological intervention on pain, function, and mood in people with knee osteoarthritis listed for total knee arthroplasty. Design: Multi-centre, mixed-methods feasibility randomized controlled trial of intervention plus usual care versus usual care. Setting: Participants’ homes or hospital. Participants: Patients with knee osteoarthritis listed for total knee arthroplasty and score >7 on either subscales of Hospital Anxiety and Depression Scale. Intervention: Up-to 10 sessions of psychological intervention (based on cognitive behavioural therapy). Main measures: Feasibility outcomes (recruitment and retention rates, acceptability of trial procedures and intervention, completion of outcome measures), and standardized questionnaires assessing pain, function, and mood at baseline, and four and six months post-randomisation. Results: Of 222 people screened, 81 did not meet inclusion criteria, 64 did not wish to participate, 26 were excluded for other reasons, and 51 were randomized. A total of 30 completed 4-months outcomes and 25 completed 6-month outcomes. Modal number of intervention sessions completed was three (range 2–8). At six-month follow-up, mood, pain, and physical function scores were consistent with clinically important benefits from intervention, with effect sizes ranging from small (d = 0.005) to moderate (d = 0.74), and significant differences in physical function between intervention and usual care groups (d = 1.16). Feedback interviews suggested that participants understood the rationale for the study, found the information provided adequate, the measures comprehensive, and the intervention acceptable. Conclusion: A definitive trial is feasible, with a total sample size of 444 people. Pain is a suitable primary outcome, but best assessed 6 and 12 months post-surgery.